2020
DOI: 10.1177/1539449220928141
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility and Efficacy of an Israeli Lifestyle Redesign®–Based Program for Well Older Adults: A Pilot Study

Abstract: The Israeli Lifestyle Program (ILP) was adapted from the original Lifestyle Redesign® intervention, aiming to enhance health, functioning, and quality of life (QoL) of older adults. The purpose of this study was to examine the feasibility and effectiveness of the ILP. The design of the study entailed a non-randomized trial with a 3-month follow-up including 18 women aged 65 to 81 recruited from a community center. The research group ( n = 9) participated in 15 weekly group meetings and three individual session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…It was found that the French‐Canadian Lifestyle Redesign® can be successfully delivered to older adults with and without disabilities by adapting it to the local context and to the participants' interests and abilities. Cultural and contextual adaptations of the programme have been frequently reported as crucial to the programme's success (Abma & Heijsman, 2015; Maeir et al, 2021), which was supported by this study's findings. These adaptations should go beyond language, values, and interests and consider older adults' functional profile and facilitators and barriers to participation for an optimal fit between their reality and the methods used in the programme.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It was found that the French‐Canadian Lifestyle Redesign® can be successfully delivered to older adults with and without disabilities by adapting it to the local context and to the participants' interests and abilities. Cultural and contextual adaptations of the programme have been frequently reported as crucial to the programme's success (Abma & Heijsman, 2015; Maeir et al, 2021), which was supported by this study's findings. These adaptations should go beyond language, values, and interests and consider older adults' functional profile and facilitators and barriers to participation for an optimal fit between their reality and the methods used in the programme.…”
Section: Discussionsupporting
confidence: 86%
“…Mountain et al, 2020) and interventions fostering social participation in older adults (Raymond et al, 2013), this intensity and duration appear necessary to develop trust, openness to others, a positive group dynamic, awareness of individual challenges, and successful behavioural changes. The high attendance and retention rates for this programme are comparable to other studies (Cassidy et al, 2017; Maeir et al, 2021; Mountain et al, 2008) and might be partly due to positive relationships between participants and with the occupational therapist. These results are supported by other studies showing the centrality of the social aspect in adherence to and better engagement in interventions (e.g.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…OT aims to improve health and well-being through engagement in occupation (American Occupational Therapy Association [AOTA], 2020). Occupation-based healthy lifestyle interventions have shown considerable improvements in life satisfaction, depression, well-being, quality of life, and social functionality of individuals (Clark et al, 2012; Eklund et al, 2017; Maeir et al, 2021). A high level of engagement in occupations was a higher positive effect on the well-being and quality of life of people with schizophrenia (Gibson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…28,29 It is noted that many lifestyle intervention programs incorporated closed group approaches with fewer than 15 participants per group and entailed one treatment session for 2 hours per week for 6 to 9 months. [26][27][28][30][31][32][33][34][35][36][37][38][39][40] However, there are foreseeable difficulties to implement lifestyle intervention with the aforementioned format in Taiwan, because it was found that community programs cannot regularly connect older adults together, let alone form several closed groups that could hold intervention activities continuously. 41 Senior Citizens Learning Camp, on the other hand, is a government sanctioned organization in Taiwan that provides classes in a large local university for older adults who live in the community close to the campus.…”
Section: A Mixed-methods Pilot Studymentioning
confidence: 99%